Hubungan Antara Kepatuhan Minum Obat (MMAS-8) Dan Kualitas Hidup (WHOQOL-BREF) Penderita Tuberkulosis Di Puskesmas Di Kota Bandung - Papeo, Dizky Ramadani Putri; Immaculata, Maria; Rukmawati, Iis (Indonesian Journal of Pharmaceutical Education, 2021)
Backgroumd: Tuberculosis (TB) is an infectious disease which is until now has not been able to be threated, i.e., because of patient non-adherence in taking anti-tuberculosis drug (ATD) Objective: The objective of this research is  to study the relationship between patients adherence in taking ATD determined by MMAS-8 questionnaire with QoL of patient determined by WHOQOL questionnaire. Method: Tuberculosis patients who undergo treatment for at least 4 weeks are the subjects in this study. This study was conducted by a cross-sectional method using the MMAS-8 and WHOQOL-BREF questionnaire of tuberculosis patients at Ibrahim Adjiand Gumuruh primary health care during March - August 2018. Result: Based on MMAS-8 questionnaire filled out by 75 patients, there was 69% of high adherence, 15% moderate,  and 16% has low adherence in taking ATD. Of the 6 characteristic factors (i.e., age, sex, occupation, income, education and length of treatment), only gender (p0.01) and occupation (p0.03) factors that influence the patient adherence significantly. Based on MMAS-8 and WHOQOL-BREF questionnaire analyses, there is only psychological health aspect (domain two) that have a significant (p = 0.01) correlated with patient adherence. Conclusion: Based on the results,the psychological health of tuberculosis patients play an important role in patient adherence.